Structural analysis of natural fiber reinforced polymer matrix composite. (2020) - Navaneethakrishnan, G.; Karthikeyan, T.; Saravanan, S.; Selvam, V.; Parkunam, N.; Sathishkumar, G.; Jayakrishnan, S.
Abstract: The conventional structural material used in construction industries like aluminum, wood and steel are depleting now a day. In this work an attempt has been made to fabricate a hybrid natural fiber composite material reinforced with vinyl ester resin. Composite are made-up with various volume percentage of Sisal and Luffa fiber by compression molding. The mechanical behavior of composite material such as tensile, impact test and flexural test are carried out as per ASTM standard. The ANSYS analyzed result shows that the mechanical properties of the composite materials have a good agreement with the conventional structural aluminum material.